β-catenin-α-catenin and actomyosin signaling differentially regulate growth cone contours and axon undulation and branching of retinal ganglion cells in situ - Lew, Valerie; Khetani, Sukaynah; Kaur, Simran; Woodward, William; Sandhu, Sukmin; Rawat, Radhika; Elul, Tamira (Frontiers in Cellular Neuroscience, 2025)
IntroductionCadherin adhesive and actomyosin signaling are key cytomechanical cues required for neuronal circuit formation, but whether they function together to sculpt developing neurons is not known. Previously, we demonstrated that a β-catenin mutant (β-catNTERM) that disrupts binding of endogenous, full length β-catenin to α-catenin in the Cadherin adhesion complex, and a pharmacological inhibitor for actin regulator, non-muscle Myosin II (Blebbistatin), resulted in growth cones with fewer and more filopodia or filopodia-like protrusions than control growth cones of retinal ganglion cells (RGCs) in brains from Xenopus laevis embryos.MethodsHere, we assessed whether perturbation of β-catenin adhesive and Myosin II signaling specifically impacted additional, diverse yet interrelated, parameters of growth cone morphology and axon pathfinding, including two novel measures of growth cone contours.ResultsAmong other findings, we show that growth cones of individual RGCs expressing β-catenin NTERM have less complex contours (lower fractal dimension) and axons that are more undulatory than control growth cones and axons. In contrast, contours of Blebbistatin exposed growth cones are less concave (lower fractional concavity) and their axons extend more branches compared to control RGCs. In additional experiments, an α-catNTERM mutant and ROCK inhibitor phenocopied the specific effects of β-catNTERM and Blebbistatin on complexity and concavity of growth cone contours.DiscussionThis data suggests that β-catenin-α-catenin and actomyosin interactions differentially regulate growth cone contours as well as axonal undulation and branching of RGCs in whole brains. Broadly, our results provide insight into cytomechanical mechanisms of neuronal circuit formation normally, and neuronal connectivity defects in human neurodevelopment disorders associated with mutations in Cadherin and β-catenin.